INDUSTRIAL REVOLUTION 4.0 AND ITS IMPACT ON THE PREPARATION OF THE WORKFORCE BY UNIVERSITIES IN INDONESIA - Amin, Muhammad; Jihan, Jihan; Sulistyo, Lilik; Solong, Najamuddin Petta; Seran, Herman Elfridus (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
Technological developments cause very significant changes in how goods and services are produced. This then causes changes in the ability needs of the community in the world of work. Higher education, as one of the educational institutions before plunging into the world of work, has an essential role in preparing this workforce. This study aims to see how the industrial revolution 4.0 affects the preparation of the workforce in Indonesia by universities. This research will be carried out using a qualitative approach. The data used in this research comes from the results of previous research and studies which still have relevance to the content of this research. This research finds that there is a debate some experts think that the total number of workers in the world will decrease, while others believe the number will remain the same. However, there is agreement that this will affect the education system, where the type of learning must change according to the needs of skills and knowledge that exist in the future so that people in the future can work according to the needs of the industry at that time.